THE INFLUENCE OF WORK MOTIVATION ON THE DISCIPLINE OF EMPLOYEES OF THE ADMINISTRATIVE DEPARTMENT OF SOREANG REGIONAL GENERAL HOSPITAL - Dewi Ayu Melati Ningsih; Siska Anisa; Dinda Putri Eka Darmayanti; Ceria Febiana (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2021)
This study aims to determine the effect of work motivation on employee discipline in the administrative division of the Soreang General Hospital. This study uses a descriptive research method with a quantitative approach, data analysis techniques: validity test, reliability test, simple linear regression test, t test and coefficient of determination test. Data collection techniques used were observation, questionnaires, literature study with the research subjects were employees of the administration division at the Soreang General Hospital as many as 24 people. The results of this study indicate a correlation of 0.653, meaning that there is a positive and strong relationship between work motivation (X) and discipline (Y) variables. While the large influence of the work motivation variable (X) on discipline (Y) is 65.3%, meaning that it is a strong influence and 34.7% is influenced by other variables. The advice given in this study is that the better the motivation possessed by an employee, the higher the discipline of the employee. Good work results are certainly based on good motivation. Conversely, if the employee's work motivation is not built properly, it will produce work results that serve as goals and can realize organizational goals, therefore it is expected that the company, especially the Soreang General Hospital, will continue to motivate its employees in improving work performance. Keywords: Work Motivation, Discipline, Soreang General Hospital